Great iPhone development level 1 - Means, W. Scott (O'Reilly Media, 2010)
"Great iPhone Development: Level 1 will teach you the fundamentals of iPhone programming, beginning with getting your development environment set up and registering with the Apple Developer Connection. You'll get a handle on XCode as well as Objective C basics, and quickly build working applications. By the time you're done, you'll have built complete applications with menus, customized and scrolling text, and rotatable displays. Throughout the course, you'll learn how the iPhone is unlike almost any other device--and how you can program for that unique user environment. The application window will be dealt with extensively, as well as menus and custom text-handling. You'll have to think about memory, too, and this course will help you debug and optimize your mobile apps."--Resource description page.
Title from resource description page (viewed November 6, 2015)
Keywords: iOS (Electronic resource); iPhone (Smartphone) -- Programming; Smartphones -- Programming; iPhone (Téléphone intelligent); Programmation; Téléphones intelligents; Programmation